“Trusted in Being the Experts of Being a Student”: Participatory Evaluation in Higher Education - Liz Austen; Alan Donnelly (Journal of Participatory Research Methods)
This report describes a participatory evaluation of a postgraduate course delivered at the University of Winchester in the UK. The PGCert/MA in Student Engagement in Higher Education utilized sector-leading practices and research to explore student engagement in contemporary higher education. As co-creation, co-design, and staff-student partnerships are integral concepts within student engagement scholarship and practice, a congruent participatory evaluation of the PGCert/MA was conducted. This approach utilized an Advisory Group of current students and graduates to co-construct a Theory of Change, design data-gathering methods, and support the synthesis of findings and associated recommendations. This report provides details of the stages of this evaluation and the participatory activities which were designed and delivered. In addition to providing a robust conclusion on the process, impact, and outcomes of the course, this report discusses the benefits and challenges of participatory evaluation.